E-LEARNING INNOVATIONS IN HIGHER EDUCATION - NICOLETA GUDANESCU; MARIA-LOREDANA POPESCU (Challenges of the Knowledge Society)
This scientific work is presenting the ways to do computer assisted education for students, giving the good practice examples, presenting new electronic learning systems, the advantages and limits and to try to emphasize that these days E-learning is one of the most efficient way to reach education at all levels, specially higher education systems. The objectives of this paper are: to explain the contribution of modern technologies and electronic systems to educational processes, to define the concept of technology based learning, to introduce the electronic tools for education, to present good practice examples in implementing E-learning systems in higher education and corporate environment in Romania and last but not least the new electronic learning systems. Introducing the computers and ITC in educational processes facilitates them and makes the educational system modern and efficient. E - learning innovations offers a core group of professional development courses designed to help anyone achieve professional advancement and personal enrichment. The programs are founded on an extensive experience and understanding of technology-based learning environments. They focus on the most current industry practices for various learning environments and best approaches for multiple learning styles. They ensure that the students get the information and skills needed to achieve more in teaching practice and to confidently enter the distance or online classroom.